2011
DOI: 10.1038/nprot.2011.400
|View full text |Cite
|
Sign up to set email alerts
|

Bar-coded hydrogel microparticles for protein detection: synthesis, assay and scanning

Abstract: This protocol describes the core methodology for the fabrication of bar-coded hydrogel microparticles, the capture and labeling of protein targets and the rapid microfluidic scanning of particles for multiplexed detection. Multifunctional hydrogel particles made from poly(ethylene glycol) serve as a sensitive, nonfouling and bio-inert suspension array for the multiplexed measurement of proteins. Each particle type bears a distinctive graphical code consisting of unpolymerized holes in the wafer structure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
153
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(155 citation statements)
references
References 49 publications
0
153
0
Order By: Relevance
“…We may be able to polymerize bifunctional particles containing a fluorescent code on the downstream edge of the particle and containing biomolecular capture probes such as DNA or antibodies in the upstream edge of the particle. These can be used for bioassays, harnessing previously shown advantages of using hydrogel particles for biosensing 30 . It is important to note that the particles considered here always align in the same direction, in contrast with particles aligned with sheath flows, such as in flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…We may be able to polymerize bifunctional particles containing a fluorescent code on the downstream edge of the particle and containing biomolecular capture probes such as DNA or antibodies in the upstream edge of the particle. These can be used for bioassays, harnessing previously shown advantages of using hydrogel particles for biosensing 30 . It is important to note that the particles considered here always align in the same direction, in contrast with particles aligned with sheath flows, such as in flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…[ 279 ] The same concept was used to multiplex detection of proteins. [ 280 ] PEG-based microparticles were obtained having a distinctive graphical code (unpolymerized holes in the wafer structure of the microparticles). This code is used to identify the antibody probe, which Tightly crosslinked polybutadiene core with ca.13 chains each of PMMA and PS protruding out of it, in separated hemispheres.…”
Section: Reviewmentioning
confidence: 99%
“…44 Due to the thermal expansion of PDMS (thermal expansion coefficient of 3.1 Â 10 À4 C À1 ), it is inevitable for compressive stress to exert the interface between PDMS layers during cooling at room temperature. To assess more quantitatively, we measured the interfacial burst pressure of PDMS (i.e., Sylgard 184) chips cured at room temperature for $100 h. For the preparation of partially cured PDMS-coated glass slides, we found that partial curing at room temperature for $22 h was optimal to avoid not only the percolation of nearly uncured PDMS into microchannels on fully cured blocks but also the immediate detachment of the micropatterned block.…”
Section: Stronger Interfacial Bonding Of Uv-cured Pdms Chipsmentioning
confidence: 99%
“…In brief, we were able to successfully increase the throughput [cycle/min] of SFL by a factor of at least 2.04 and of up to 3.64 by reducing the cycle time to 440 ms, compared with a typical cycle time range of 900-1600 ms. 16,44,49 We performed the SFL experiment with a cycle time of 900 ms with a conventional PDMS chip as a conservative control (Table I). …”
Section: E Enhanced Productivity Of Stop Flow Lithography With Uv-cumentioning
confidence: 99%